Anonymous
Anonymous asked in 科學及數學數學 · 1 decade ago

F.2Maths!!!!!!!!!!!40p!!!!!!

5. Factorize the following expressions.

(a) 36a^2− 9

(b) 27 − 12b2

(c) 2s2− 50t2 (d) 180u2− 20v2

6. Factorize the following expressions.

(a) 245a2

+ 210ab + 45b2

(b) 72a2

+ 168ab + 98b2

(c) 81a2

+ 36b2

+ 108ab

(d) 44a2

+ 99b2

+ 132ab

7. Factorize the following expressions.

(a) 28a2

− 140ab + 175b2

(b) 45a2

− 120ab + 80b2

(c) 2x2

+ 2y2

− 4xy

(d) 12x2

+ 3y2

− 12xy

8. Factorize the following expressions.

(a) (x − y)2

− 25

(b) 64 − (a + b)2

(c) x^2

− (2x + 5y)^2 (d) 9p^2

− (4p − 5q)^2

Update:

唔駛做NO.8

2 Answers

Rating
  • 1 decade ago
    Favorite Answer

    5. Factorize thefollowing expressions.

    (a) 36a ^2− 9

    =9( 4a ^2-1)

    =9( 2a +1)( 2a-1)

    (b) 27 − 12b^2

    =3(9-4b^2)

    =3(3+2b)(2-2b)

    (c) 2s^2− 50t^2

    =2(s^2-25t^2)

    =2(s+5t)(s-5t)

    (d) 180u^2− 20v^2

    =20(9u^2-v^2)

    =20(3u+v)(3u-v)

    6. Factorize the following expressions.

    (a) 245a ^2+ 210ab+ 45b^2

    =5( 49a ^2+42ab+9b^2)

    =5( 7a +3b)^2

    (b) 72a ^2+ 168ab+ 98b^2

    =2( 36a ^2+84ab+49b^2)

    =2( 6a +7b)^2

    (c) 81a ^2++ 36b^2+108ab

    =9( 9a ^2+12ab+4b^2)

    =9( 3a +2b)^2

    (d) 44a ^2+ 99b^2+132ab

    =11( 4a ^2+12ab+9b^2)

    =11( 2a +3b)^2

    7. Factorize the following expressions.

    (a) 28a ^2− 140ab+ 175b^2

    =7( 4a ^2-20ab+25b^2)

    =7( 2a-5b)^2

    (b) 45a ^2− 120ab+ 80b^2

    =5( 9a ^2-24ab+16b^2)

    =5( 3a-4b)^2

    (c) 2x^2+ 2y^2− 4xy

    =2(x^2-2xy+y^2)

    =2(x-y)^2

    (d) 12x2+ 3y2− 12xy

    =3(4x^2-4xy+y^2)

    =3(2x-y)^2

    8. Factorize the following expressions.

    (a) (x − y)^2− 25

    =(x-y+5)(x-y-5)

    (b) 64 − (a + b)^2

    =(8+a+b)(8-a-b)

    (c) x^2− (2x + 5y)^2

    =(x+2x+5y)(x-2x-5y)

    =-(3x+5y)(x+5y)

    (d) 9p^2− (4p− 5q)^2

    =(3p+4p-5q)(3p-4p+5q)

    =(7p-5q)(5q-p)

    • Commenter avatarLogin to reply the answers
  • 1 decade ago

    (a) 36a^2− 9

    9(4a^2-1)

    (b) 27 − 12b2

    3(9-4^2)

    (c) 2x2+ 2y2− 4xy

    2(x2+y2-2xy)

    2(x2-2xy+y2)

    2(x+y)^2

    Source(s): me,i am busy
    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.